2017
DOI: 10.1021/acsami.6b12677
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Localized Growth of Ordered Metal Oxide Hollow Sphere Array on Microheater Platform for Sensitive, Ultra-Fast Gas Sensing

Abstract: A simple and versatile strategy is presented for the localized on-chip synthesis of an ordered metal oxide hollow sphere array directly on a low power microheater platform to form a closely integrated miniaturized gas sensor. Selective microheater surface modification through fluorinated monolayer self-assembly and its subsequent microheater-induced thermal decomposition enables the position-controlled deposition of an ordered two-dimensional colloidal sphere array, which serves as a sacrificial template for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 54 publications
0
47
0
1
Order By: Relevance
“…12 Meanwhile, it is indicated that it becomes easier for gas molecules to access thin nanobridges in ordered nanostructures, which facilitates the sensing process. [82][83][84] The results of both 2D IO structures and 2D hollow hemispheres clearly reveal that the 2DOM nanostructures are promising nanoarchitectures to simultaneously achieve high and rapid response. In addition, the ordered frame matrix would be robust in tolerating the compressive and tensile stresses experienced during the heating/cooling operations due to the more uniform force distribution in ordered porous lms, which can yield higher sensing stability.…”
Section: D Macroporous Arrays For Gas Sensingmentioning
confidence: 96%
“…12 Meanwhile, it is indicated that it becomes easier for gas molecules to access thin nanobridges in ordered nanostructures, which facilitates the sensing process. [82][83][84] The results of both 2D IO structures and 2D hollow hemispheres clearly reveal that the 2DOM nanostructures are promising nanoarchitectures to simultaneously achieve high and rapid response. In addition, the ordered frame matrix would be robust in tolerating the compressive and tensile stresses experienced during the heating/cooling operations due to the more uniform force distribution in ordered porous lms, which can yield higher sensing stability.…”
Section: D Macroporous Arrays For Gas Sensingmentioning
confidence: 96%
“…One of the most advantages of "CIJ" is a lower probability of nozzle obstruction due to the working of jetting system at all time. The major disadvantages of CIJ systems are the problem in sizes controlling, generating satellite, and splattering of the droplets on the target [9,10]. In DOD, droplets are formed alternatively by the piezoelectric properties in response to discontinued pulses and pressures, respectively.…”
Section: Modeling Of Dod Jettingmentioning
confidence: 99%
“…For example, HHMSs have been frequently investigated as nano-reactors and drug-delivery carriers, in electromagnetic wave absorption, 3,4 as well as in photocatalysis 5 and as active compounds in gas sensors 6 and in photovoltaic devices. [7][8][9] In recent years, the focus on HHMSs has shifted to their use as anode materials in lithium ion batteries (LIBs) and, recently, sodium-ion batteries (SIBs).…”
Section: Introductionmentioning
confidence: 99%